Why hate carbon taxes? Machine learning evidence on the roles of personal responsibility, trust, revenue recycling, and other factors across 23 European countries. (March 2021) - Levi, Sebastian
Abstract: Carbon taxes are considered a key instrument for achieving deep decarbonization but are often unpopular among voters. While existing studies indicate that public opposition to carbon taxes is influenced by climate change belief and by political trust, less is known about the relevance of other factors. Moreover, it remains unclear why people oppose carbon taxes more fiercely than other climate policies. To enhance understanding of carbon tax opposition, I synthesize and categorize 28 conditions that potentially provoke public opposition to carbon taxes, assess their independent importance for predicting carbon tax opposition, and review the specific form in which they predict carbon tax opposition. This analysis draws on data from approximately 44, 400 individuals from 23 European countries. It uses a random forest model, a machine learning method, to estimate independent prediction effects. The results identify the feeling of personal responsibility for trying to reduce climate change as the most important condition for predicting opposition to carbon taxes and for predicting attitudes on other climate policies. Political trust, in contrast, strongly predicts carbon tax opposition but not attitudes on other climate policies, suggesting that low political trust could explain the peculiar public aversion against carbon taxes. Recycling revenues from existing carbon prices back to households, often considered crucial for securing public support, is only associated with minor increases in the acceptance of higher carbon taxes. Finally, the results reveal that age, market liberal values, and good governance are related to carbon tax opposition in a non-monotonous pattern.